2016
DOI: 10.1002/pds.4006
|View full text |Cite
|
Sign up to set email alerts
|

Positive predictive values of selected hospital discharge diagnoses to identify infections responsible for hospitalization in the French national hospital database

Abstract: Hospitalizations for infection codes have very good PPVs in the Programme de Médicalisation des Systèmes d'Informations. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…Using nationwide register-based data on the entire French population provided a large sample size, allowing for sufficient power to perform comprehensive and multiple subgroups analyses on the risk of acute arterial events. Additionally, several studies have found the reliability, validity and accuracy of medical coding in the French administrative database for various diseases to be good 38–42. The identification of acute arterial events in the present study was similar to that in a previous study, based on the same inpatient database, reporting an increased risk of acute arterial events in patients with IBD compared with the general population 2…”
Section: Discussionsupporting
confidence: 85%
“…Using nationwide register-based data on the entire French population provided a large sample size, allowing for sufficient power to perform comprehensive and multiple subgroups analyses on the risk of acute arterial events. Additionally, several studies have found the reliability, validity and accuracy of medical coding in the French administrative database for various diseases to be good 38–42. The identification of acute arterial events in the present study was similar to that in a previous study, based on the same inpatient database, reporting an increased risk of acute arterial events in patients with IBD compared with the general population 2…”
Section: Discussionsupporting
confidence: 85%
“…32 Although identification of infection was based on discharge diagnosis only, the validity of our outcomes was recently assessed, with more than 95% accuracy of recorded cases and type of infections. 23 In addition, incidence rates of serious infections in patients exposed to anti-TNFs reported in our study are similar to those reported in the TREAT registry. The increased risk associated with thiopurines or anti-TNFs compared with unexposed patients reported in our study may also strengthen the external validity of our findings.…”
Section: August 2018supporting
confidence: 89%
“…Within this database, the diagnoses of infection requiring hospitalization and the type of infection have been shown to be accurate in 97% and 98% of the cases, respectively. 23 Serious infections were classified according to infection sites. These included pulmonary; gastrointestinal; skin; urinary tract; ear, nose and throat; musculoskeletal; and other infections (including sepsis, nonclassified opportunistic, and mycobacterial infections).…”
Section: Discussionmentioning
confidence: 99%
“…Excluded health insurance schemes relate to specific professions and do not depend on comorbidities or medical conditions. Several studies have assessed the reliability of the recorded information and the accuracy of its coding in different fields . Moreover, the PMSI and SNIIRAM have been used to measure disease incidence and identify determinants of medical conditions in various fields …”
Section: Methodsmentioning
confidence: 99%